Etnomatematika Sebagai Inovasi Pembelajaran dalam Mengintegrasikan Nilai Kearifan Lokal dan Konsep Matematika untuk Meningkatkan Hasil Belajar Siswa Madrasah Ibtidaiyah - Sofiyudin Arif; Umi Mahmudah (LPPM IAINU Kebumen, 2022)
This study aims to analyze the effectiveness of the implementation of ethnomathematics learning in improving student achievement in Islamic elementary schools. This research is focused on the learning outcomes of the flat wake concept. Internalization of local wisdom values in the concept of mathematics as an innovation carried out by educators in understanding students as well as providing direct learning experiences in the real world. This research applies a quantitative approach. A total of 25 students were sampled in this study which were taken randomly. Methods of collection and use of test sheets. Data analysis used paired sample t-test. The results of the hypothesis test indicated that the H0 decision was rejected (tcount = 6.297, ttable = 2.069, and and p-value = 0.000). These results indicate that there are differences in the average results of mathematics when learning mathematics internalizes local traditional values in society. These results have implications that the implementation of ethnomathematics can improve mathematics learning achievement.